2005
DOI: 10.1128/jvi.79.21.13509-13518.2005
|View full text |Cite
|
Sign up to set email alerts
|

CD8 T Cells Require Gamma Interferon To Clear Borna Disease Virus from the Brain and Prevent Immune System-Mediated Neuronal Damage

Abstract: Borna disease virus (BDV) frequently causes meningoencephalitis and fatal neurological disease in young but not old mice of strain MRL. Disease does not result from the virus-induced destruction of infected neurons. Rather, it is mediated by H-2 k -restricted antiviral CD8 T cells that recognize a peptide derived from the BDV nucleoprotein N. Persistent BDV infection in mice is not spontaneously cleared. We report here that N-specific vaccination can protect wild-type MRL mice but not mutant MRL mice lacking g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
37
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 73 publications
1
37
0
Order By: Relevance
“…This effect is most likely mediated primarily by IFN-␥ signaling within infected neurons, in similarity to what has been described in Sindbis virus, Borna virus, TMEV, and measles virus studies (7,23,38,42). However, we cannot rule out additional mechanisms.…”
Section: Discussionmentioning
confidence: 74%
“…This effect is most likely mediated primarily by IFN-␥ signaling within infected neurons, in similarity to what has been described in Sindbis virus, Borna virus, TMEV, and measles virus studies (7,23,38,42). However, we cannot rule out additional mechanisms.…”
Section: Discussionmentioning
confidence: 74%
“…To address this question, we took advantage of the BDV mouse model system for the following main reasons: (i) the infection of mice with BDV is limited to the central and peripheral nervous systems (12; also our unpublished results); (ii) BDV infections are noncytolytic, and the virus is spread mostly if not exclusively by cell-to-cell contacts (29); (iii) CD8 T cells mediate immunity to BDV (14,16) 6 N-specific CD8 T cells each by the intracerebral (CD8 i.c. ; A and B) or the intravenous (CD8 i.v.…”
Section: Discussionmentioning
confidence: 99%
“…Indirect evidence suggesting that MHC-I expression occurs on neurons includes studies in knockout mice which revealed a role of MHC-I in the activity-dependent remodeling and plasticity of neuronal connections in the central nervous system (CNS) (24). The fact that certain viral CNS infections can be controlled by CD8 T cells is further indirect evidence for MHC-I expression on neurons (16,26,31,36,47). However, in most cases the specificity of the CD8 T cells responsible for virus clearance was ill defined, and the contributions of antigen presentation by other cell types remained unclear.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This results in preventing the initiation of inflammation and progression of the autoimmune symptoms. Secondly, when dysfunctional lymphocytes are released into the mainstream, the immune system minimizes their ability to interact with triggers (antigens) through direct and indirect effects [6][7][8]. This results in a significant reduction in the severity of potential inflammatory response.…”
Section: Introductionmentioning
confidence: 99%